Análise da correlação dos sinais eletromiográficos e da acelerometria do tremor fisiológico em diferentes faixas etárias - Cury, Lacordaire Kemel Pimenta (2011)
One of the Characteristics of human aging is the loss of muscle and bone mass, which jeopardizes quality of life and increases the possibility of emerging neuromuscular diseases, such as quivers. There are several studies that seek to find ways to diagnostics or characterizations of the effects of organic loss. Usually measuring tools of neuromuscular signs are used, such as the electromyography (EMG), and the accelerometry, whose records, after collection and process, allows the application of statistic tools that eases the analyses, correlation and comparison. This study made use of a linear discriminant analysis tool (LDA),to appraise the signs collected by both these instruments, at rest and in motion, seeking to find a correlation which demonstrated the changes of the signs with aging. Accelerometry and EMG data of 59 individuals (29 Men and 30Women), aged between 24 and 87 years old, where collected, all lacking clinical signs of neuromuscular disorders or degenerative diseases. The sample was separated in seven groups, by age of decades(20-29, 30-39, 40-49, 50-59, 60-69,70-79, 80-89). 16 statistical characteristics of EMG and accelerometry sings where used, correlating them with the age of the volunteers and with each other. There were no significant correlations found between these individual factors and the age, for any of the measuring tools. Subsequently, a linear discriminant analysis tools (LDA) was used to convert, on an one-dimensional manner, the characteristics of each individual, for both measuring forms. With the correlation being done between the LDA measures and the age, a significant correlation coefficient (r> 0.8) was found, which demonstrated changes in the EMG and the accelerometry of physiological quivers with the aging.